Semiotic Analysis of Islamic Communication Message of Melengkan at Gayonese Culture in Central Aceh - Marhamah, Marhamah; Agustina, Linur Ficca (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This study discusses the forms of the message and the principles of Islamic communication at Gayo ethnic culture in Central Aceh District. Using qualitative research with the semiotics analysis approach in analysing the text of the customary speech written by A.R. Hakim Aman Pinan, this research found that the form of messages contained in the custom of downcast is the form of informative messages namely messages spoken by pemelengkan only in the form of persuasive messages, namely pemelengkan give advice containing persuasion so that awareness arises in the communicant, and coercive messages, namely pemelengkan give orders to comply with customs and sanctions against these violations. Additionally, the principles of Islamic communication contained this culture are the principle of qaulan sadiddan, qaulan kariman, qaulan layyinan, qaulan maysuran, and qaulan ma’rufan.